TBP induced double cloud point in aqueous EO13PO30EO13 solutions: investigating the evolution of associated micellar characteristics as a function of temperature. Issue 11 (7th February 2015) - Ganguly, R.; Kumar, S.; Nath, S.; Sharma, J. N.; Aswal, V. K.
<x xml:space="preserve">Abstract</x> TBP solubilized Pluronic L64 solutions exhibit inter-micellar attraction driven micellar cluster formation upon cooling, which is unique in non-ionic micellar systems.